2020
DOI: 10.3390/ijerph17041249
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Women’s Work-Family Multiple Role and Role Combination on Depressive Symptoms in Korea

Abstract: This study set out to investigate the effects of multiple roles on depressive symptoms in women. The role of women was divided into worker, household worker, spouse, parent, and caregiver roles to identify the differences in depressive symptoms according to the number of roles, role-fulfillment, and role-combination. Using the sixth raw data of the 2016 Korean Longitudinal Survey of Women and Families for analysis, the data had 6198 respondents who did not have missing values in the major variables. There are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 37 publications
1
12
0
2
Order By: Relevance
“…Although women’s economic activities have positive effects on the improvement of social role and status, on-going gender disparities in the workplace, despite new enforcement of the Sex Discrimination Act, still endanger women’s mental health [ 25 ]. Traditional gender roles such as domestic area of housework, parenting, and caregiving, are expected [ 26 ], which may induce a negative psychological burden and stress among working women.…”
Section: Discussionmentioning
confidence: 99%
“…Although women’s economic activities have positive effects on the improvement of social role and status, on-going gender disparities in the workplace, despite new enforcement of the Sex Discrimination Act, still endanger women’s mental health [ 25 ]. Traditional gender roles such as domestic area of housework, parenting, and caregiving, are expected [ 26 ], which may induce a negative psychological burden and stress among working women.…”
Section: Discussionmentioning
confidence: 99%
“…Informal care is more common among women than among men, which could lead to a higher number of subjectively reported needs among women ( 14 ). Multiple roles for women have been well-documented ( 15 ). The results of one study showed that women who combined multiple roles were less depressed and had less depressive symptoms than women who only had the role of an informal caregiver ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple roles for women have been well-documented ( 15 ). The results of one study showed that women who combined multiple roles were less depressed and had less depressive symptoms than women who only had the role of an informal caregiver ( 15 ). Even if women are believed to enjoy the informal caregiver role ( 16 ), they face diverse challenges that affect well-being and quality of life ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…The data used stratification and multistage sampling design using Korean Population and Housing Census data to ensure a representative sample. The survey collected data using the Computer Assisted Personal Interviewing (CAPI) ( 13 ) method. The KLoWF includes basic questions about the household, such as income level and type of housing; family-values-related questions; questions about personal experiences, such as marital life, family relations, and health; and questions about working conditions, such as job satisfaction and maternity leave.…”
Section: Methodsmentioning
confidence: 99%